2021
DOI: 10.1002/jae.2815
|View full text |Cite
|
Sign up to set email alerts
|

When are instruments generated from geographic characteristics in bilateral relationships invalid?

Abstract: Summary In their highly influential paper, “Does Trade Cause Growth?,” Frankel and Romer estimate a trade equation to predict bilateral trade shares, which are in turn aggregated to construct an instrument for trade openness in income regressions. The Frankel‐Romer approach has gained widespread popularity as a method to generate instruments for trade and many other outcome variables from estimated bilateral relationships. In this paper, we show analytically and empirically that the Frankel–Romer instrument gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…As shown by Deij et al (2021), this gives consistent results regardless of whether the absence of reported trade is due to no trade, misreported data entry, or that the data are not published.…”
Section: Exclusion Restrictionssupporting
confidence: 65%
See 4 more Smart Citations
“…As shown by Deij et al (2021), this gives consistent results regardless of whether the absence of reported trade is due to no trade, misreported data entry, or that the data are not published.…”
Section: Exclusion Restrictionssupporting
confidence: 65%
“…The robustness checks give no evidence of a violation of the exclusion restrictions. First, the results are robust to the inclusion of out-of-sample bilateral trade predictions that are used to form the instrument, which is shown by Deij et al (2021) to be an important check for exclusion restrictions when the instruments are generated from the gravity model. Second, we show that migration and trade are determined by different geographic characteristics, suggesting that the exclusion restriction is not violated because the geographic instruments capture the income effects of immigration.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 92%
See 3 more Smart Citations